Development and validation of a structured survey questionnaire on knowledge, attitude, preventive practice, and treatment-seeking behaviour regarding dengue among the resident population of Sabah, Malaysia: an exploratory factor analysis - Rhanye Mac Guad; Ernest Mangantig; Wah Yun Low; Andrew W. Taylor‑Robinson; Meram Azzani; Shamala Devi Sekaran; Maw Shin Sim; Nornazirah Azizan (Springer Nature, 2021)
Background: Several studies have reported a significant association of knowledge, attitude and preventive practice (KAP) regarding dengue infection among community’s resident in endemic areas. In this study we aimed to assess and develop a reliable and valid KAP survey on the subject of dengue that is suitable for the resident population of Sabah, Malaysia. Methods: A community-based cross-sectional study was conducted from October 2019 to February 2020 involving 468 respondents. Information on the socio-demographic characteristics of the participants (six items), their KAP (44, 15 and 18 items on knowledge, attitude and practice, respectively) and treatment-seeking behaviour (five items) towards dengue was collected using a structured questionnaire. Data analysis was performed using SPSS and R software in the R Studio environment. The knowledge section was analysed by two-parameter logistic item response theory (2-PL IRT) using ltm package. The construct validity and reliability of items for sections on attitude, practice and treatment-seeking behaviour were analysed using psy package. Results: For the knowledge section, only 70.5% (31/44) of items were within or close to the parameter acceptable range of −3 to+3 of difficulty. In terms of discrimination, 65.9% (29/44) of items were within or close to the accept‑ able range of 0.35 to 2.5, and 24 items (54.5%) failed to ft the 2-PL IRT model (P<0.05) after assessing by goodness of-fit analysis. Only eight items were reliable and retained in the attitude section with a Kaiser–Meyer–Olkin (KMO) test value of>0.7, while based on the communalities, 11 items in the attitude section were excluded due to very low h2, factor loading values and low correlation with the total (<0.5). The practice section was found suitable for factor analysis because the KMO value was>0.7. The communalities of the practice section showed that seven items had low h2 values (<0.3), which were therefore excluded from further analysis, and only 11 items were retained. Conclusions: The KAP items retained in the final version of the survey were reliable and valid to be use as a questionnaire reference when conducting future similar studies among the population of Sabah.